2013
DOI: 10.1016/j.jhep.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Independent, parallel pathways to CXCL10 induction in HCV-infected hepatocytes

Abstract: Background & Aims The pro-inflammatory chemokine CXCL10 is induced by HCV (hepatitis C virus) infection in vitro and in vivo, and is associated with outcome of IFN (interferon)-based therapy. We studied how hepatocyte sensing of early HCV infection via TLR3 (Toll-like receptor 3) and RIG-I (retinoic acid inducible gene I) led to expression of CXCL10. Methods CXCL10, type I IFN, and type III IFN mRNAs and proteins were measured in PHH (primary human hepatocytes) and hepatocyte lines harboring functional or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 47 publications
3
40
0
Order By: Relevance
“…Although type I and type III IFNs induce formation of the ISGF3G complex that binds ISREs (1, 50), we previously observed no contribution of these cytokines to CXCL10 induction in immortalized cell lines, as described above (44). We hypothesized that one or more IRFs may be directly binding to the CXCL10 promoter.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Although type I and type III IFNs induce formation of the ISGF3G complex that binds ISREs (1, 50), we previously observed no contribution of these cytokines to CXCL10 induction in immortalized cell lines, as described above (44). We hypothesized that one or more IRFs may be directly binding to the CXCL10 promoter.…”
Section: Resultsmentioning
confidence: 80%
“…We recently showed that both TLR3 signaling and RIG-I signaling are required for CXCL10 induction in hepatocytes during early HCV infection but that the initial induction did not require type I or type III IFNs (44). Therefore, in this study we sought to identify the transcription factors activated downstream of TLR3 and RIG-I that contribute to HCV-mediated CXCL10 induction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations